Csvpwm Algorithm for Induction Motor Drive Implementation Using Dspace - Y.CHINTU SAGAR., S. ABDUL RAZAK MIAH, S. FARZANA (Mathematical Statistician and Engineering Applications, 2023)
Abstract: This paper presents performance of conventional space vector based pulse width modulation (CSVPWM) algorithm for voltage source inverters fed INDUCTION MOTOR drive using dSPACE. The proposed algorithm is valid for advanced modulation indicators. To reduce the harmonious distortion and to increase the dc bus application of the inverter when compared with the sinusoidal PWM (SPWM) algorithm, this paper has been concentrated on the perpetration of conventional space vector based PWM algorithm. The main purpose of this system work is to determine whether dSPACE can be used in controlling power electronics operations. From the test done, control of induction motor was successfully executed using dSPACE which means this process is attainable. The proposed PWM algorithms have been developed by using the generalization of sector selection. To validate the proposed algorithm, numerical simulation and real time studies have been carried out and results are presented.